PERAN BMT DALAM PEMBERDAYAAN EKONOMI (STUDI KASUS PADA PEMBIAYAAN BMT PADI BERSINAR UTAMA SURABAYA) - Evi Nur Fitria; A. Syifa'ul Qulub (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
For those who have entered the productive age and are able to work, without high education and business capital, the possible work will be to open employment opportunities in the micro business sector. The role of the small business in practice is constrained by several things, one of which is the problem of capital. This research aims to find out how the role of Baitul Maal Wat Tamt BMT Pinar Bersinar Utama Surabaya towards the economic empowerment of small traders in the Pucang Market Surabaya. The research method used is a qualitative case study approach using data collection techniques carried out by interviews and direct observation to the object of research. The results of this study are Baitul Maal Wat Tamwil has played a role in increasing the business of small traders in the Pucang Market in Surabaya. Business improvement from small traders can be seen from BMT members who trade in the Pucang Market experiencing increased revenue and smooth business from time to time.Keywords: Baitul Maal Wat Tamwil, Economic Empowerment, Financing